Penilaian outcome dan impak program-program peningkatan prestasi sekolah di sekolah-sekolah berprestasi tinggi di Negeri Kedah dan Terengganu - Kasim, Abd Latif; Daud, Yaakob; Don, Yahya; Sin, Ishak; Hamid, Ghazali; Puteh, Alis; Md Ali, Kamarulzaman; Mansor, Nordin; Yob, Abd Rahman (Universiti Utara Malaysia, 2012)
This study was aimed to identify the students' perspective for evaluating outcome and impact of performance enhancement programs in high performance schools in Kedah and Terengganu. Furthermore, the study also aimed to examine different perspectives on the evaluation of outcomes and impact of the program in different states through the four key dimensions namely attitude, learning, confidence, and quality of service.This quantitative study had used a cross sectional survey to collect data on the current situation of students' perspective on program outcome and impact assessment.The population of this study involves students participating in courses and programs to increase student performance in high performance schools at Kedah and Terengganu.Clustered random sampling technique was used to select a simple random sampling from a population study.The instrument used was through the construction of the questionnaire and tested the validity and reliability of the study items. Analysis of the survey data was done using the SPSS (Statistical Package For Social Science) version 18.0.The descriptive data analysis had involved as frequency and percentage of respondents, while the second part of inferential analysis was to test the research hypotheses using Pearson correlation test, T-test, and ANOVA. The results showed there was a difference and a significant positive relationship on the dimensions of attitude and the quality of school services.The results also revealed that the quality of service plays an important role in influencing students and the effectiveness school programs were implemented. Consequently, the student perspective on attitude, learning, confidence, and quality of service should be considered as an important element in the planning of programs for enhancing their skills and improving the quality of school services especially high performance schools that have been recognized as a model school to all schools in Malaysia.